Teaching Philosophy to Students; Necessities, Prerequisites and International Experiences - Mohammmad Amini; Ali Yazdkhasty (Comparative Education Society of Iran ( CESIR), 2019)
In the world brimming with rapid changes and developments of the 21st century and mass of various data and information, teaching philosophy to students in the meaning of teaching the correct ways of thinking, obtaining information, reasoning as well as critical and evaluative thinking would be deemed as a universal necessity and the basic responsibility of all educational systems of the various countries. The reason lies behind the fact that teaching philosophy to learners, on the one hand, lays the grounds for development of students' intellectual and cognitive power, and on other hand, facilitates settling the personal and social problems by its manifestation in real and practical life. Having recognized the importance of teaching philosophy to students, this paper aims to highlight the crucial role and responsibility of educational system in this realm, and accordingly, attempts to prepare the preliminaries for legalization of teaching philosophy and including it in the curricula of schools and educational centers.